Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1002/(sici)1099-0852(199608)5:3<155::aid-car250>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse and Sudden Infant Death

Abstract: In times past, parents were usually blamed when an infant died suddenly and unexpectedly. A more caring attitude evolved with the adoption of the term 'cot death' or 'sudden infant death syndrome' (SIDS). Recent research looking at the factors responsible for SIDS has focused on aspects of child care and parental behaviour.Epidemiological studies confirm that several risk factors associated with child maltreatment are also to be found in many families who experience a sudden infant death. Social deprivation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…SIDS was introduced as a registerable cause of death in the United Kingdom in 1971. It comprises a subcategory of sudden unexpected deaths in infancy (SUDI) and "ill-defined deaths" (Fleming, Blair, Bacon, & Berry, 2000;Hobbs & Wynne, 1996) and accounts for the largest single category of deaths in England and Wales for infants between the ages of 1 month and 1 year . Statistics from the United States (Anderson & Smith, 2003National Center for Health Statistics, 2004), Canada (Health Canada, 2003;Public Brookman, Nolan / Dark Figure of Infanticide 879 Health Agency of Canada, 1998Canada, , 1999, and Australia (Al-Yaman, Bryant, & Sargeant, 2002; Australian Institute of Health and Welfare [AIHW], personal communication, April 4, 2005;Child andYouth Health, 2002, 2003) all similarly indicate that although the rate of SIDS has declined considerably during the past decade, it remains the leading cause of death for postneonatal infants (i.e., those aged between 1 month and 1 year) and constitutes the third largest category of infant death overall in these countries.…”
Section: Sidsmentioning
confidence: 99%
See 1 more Smart Citation
“…SIDS was introduced as a registerable cause of death in the United Kingdom in 1971. It comprises a subcategory of sudden unexpected deaths in infancy (SUDI) and "ill-defined deaths" (Fleming, Blair, Bacon, & Berry, 2000;Hobbs & Wynne, 1996) and accounts for the largest single category of deaths in England and Wales for infants between the ages of 1 month and 1 year . Statistics from the United States (Anderson & Smith, 2003National Center for Health Statistics, 2004), Canada (Health Canada, 2003;Public Brookman, Nolan / Dark Figure of Infanticide 879 Health Agency of Canada, 1998Canada, , 1999, and Australia (Al-Yaman, Bryant, & Sargeant, 2002; Australian Institute of Health and Welfare [AIHW], personal communication, April 4, 2005;Child andYouth Health, 2002, 2003) all similarly indicate that although the rate of SIDS has declined considerably during the past decade, it remains the leading cause of death for postneonatal infants (i.e., those aged between 1 month and 1 year) and constitutes the third largest category of infant death overall in these countries.…”
Section: Sidsmentioning
confidence: 99%
“…Other researchers have argued that the SIDS term is used to avoid a more thorough autopsy, to "mercifully" conclude investigations where child abuse may be suspected (Nam, Eberstein, & Deeb, 1989) and to "avoid awkward truths" (Meadow, 1999, p. 12). It is suggested that SIDS has become synonymous with a natural death (Hobbs & Wynne, 1996;Meadow, 1999) and is thus a "seductive" diagnosis-one that protects parents and professionals, absolving them from all sense of guilt (Emery, 1993b). Similarly, Reder and Duncan (1999) and Wilczynski (1994Wilczynski ( , 1997 have pointed to a general reluctance on the part of pathologists and coroners to act on suspected cases of filicide, particularly in ambiguous situations where there is no conclusive proof to support their suspicions (as can be the case in many instances of SIDS).…”
Section: Sidsmentioning
confidence: 99%